Language on Bemo in Kupang: A Landscape Linguistic Approach - Daniel F. Kamengko; Alfred Snae; Nanian N Benu (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This article discusses signs in the form of writing in public spaces, especially found on bemo (public transportation) in Kupang city through a linguistic landscape approach. The topics discussed are the language used, the form of the language, the dominance of the language, and the perception of the people. Data were obtained from photographs with digital cameras and interviews with informants and then analyzed qualitatively. As a result, the language used on the bemo is multilingual and dominated by English in the form of words, phrases, clauses, sentences, and acronyms. English dominates in each lingual unit except in the form of acronyms. Regarding the use of language in public spaces, especially the written language found on bemo, people feel happy if they find their language visible in public spaces. Therefore, the respondent expected and suggested that it is important to maintain their language. However, they are aware that their mother tongue cannot help in terms of the economy, therefore, government intervention through local language policies is needed for the language survival.